THE IMPORTANCE OF INFORMATION TECHNOLOGY AND ARTIFICIAL INTELLIGENCE IN DEPRESSION - Ibodullayev Z.R; Maxamatjanova N.M.; Gafurova S.SH; Dursunov S.A. (The Bioscan, 2024)
Depression is a mental illness that affects millions of people worldwide, reducing quality of life and negatively impacting a person's social life. Depression is often undiagnosed, patients seek treatment late, mental health professionals are in short supply, and access to treatment services is limited for patients living on difficult roads. New technologies, particularly artificial intelligence (AI), have tremendous potential in the field of mental health to improve the diagnosis and effective treatment of depression. Artificial intelligence is ushering in a new era in the diagnosis, treatment and support of patients with depressive disorders. In this article, we examine the role and potential of artificial intelligence in the treatment of depressive disorders, as well as discuss the threats associated with the use of such technology.